Daily rhythm and seasonal pattern of lick use in sika deer (Cervus nippon) in China. Issue 3 (4th May 2019) - Li, Weiqi; Li, Chunwang; Jiang, Zhigang; Guo, Rui; Ping, Xiaoge
Abstract: Many ungulates are reported to use natural or artificial licks with seasonal patterns around the world. From December 2016 to August 2017, we used infrared camera to record the use of artificial licks in wild sika deer ( Cervus nippon ) in Zhejiang Qingliangfeng National Nature Reserve, China. We explored the daily rhythm, seasonal pattern and sex difference in lick utilization. In total, 12, 043 videos and 22, 901 pictures were collected. Our results showed that: (1) the lick visiting frequency was higher at night than that during daytime; (2) the difference in lick visiting frequency between females and males disappeared after taking into account of sex ratio; (3) the lick duration peaked in April during a year. These findings suggested that there were clear daily rhythm and seasonal pattern of lick use in sika deer. Seasonal change in lick use intensity was consistent with our prediction. These variations in lick use might be driven by both the physiological needs of the mineral elements in different life stages and the seasonal changes in climate and food. The reserve management authority should pay more attention to the supplement of licks in spring and summer to fulfill animal's physiological needs.